2004
DOI: 10.1111/j.1365-2265.2004.02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of fine‐needle aspiration for diagnosis of carcinoma associated with multinodular goitre

Abstract: Thyroid fine needle aspiration is not useful for differentiating MNG with malignant degeneration from benign MNG, as more than 80% of carcinomas go unnoticed; it provides a sensitivity of 17% for detecting carcinomas, rising to 26% if microcarcinomas are excluded. We therefore suggest that clinical criteria should prevail over FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
2
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 31 publications
5
45
2
4
Order By: Relevance
“…Although FNAB is a reliable diagnostic technique, it is not a perfect guide in decision making for operative or nonoperative treatment of multinodular goiter. 6 In patients with thyroid carcinoma, a single false-negative result of FNAB was associated with a 28-month delay in surgical treatment, and these patients had higher rates of local invasion and persistent disease. 7 False-negative results of FNAB resulted in underestimation of clinical findings associated with thyroid carcinoma.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FNAB is a reliable diagnostic technique, it is not a perfect guide in decision making for operative or nonoperative treatment of multinodular goiter. 6 In patients with thyroid carcinoma, a single false-negative result of FNAB was associated with a 28-month delay in surgical treatment, and these patients had higher rates of local invasion and persistent disease. 7 False-negative results of FNAB resulted in underestimation of clinical findings associated with thyroid carcinoma.…”
Section: Commentmentioning
confidence: 99%
“…4,5 However, as many as 80% of thyroid carcinomas can be undetected at FNAB in most patients with multinodular goiter. 6 False-negative results of FNAB cause substantial delay in surgical treatment of thyroid carcinoma, leading to local invasion in some patients. 7 Current diagnostic methods may not enable detection of the malignant nature of a thyroid nodule, especially in multinodular goiter; therefore, new techniques are being investigated to improve the evaluation of thyroid nodules.…”
Section: T He Primary Indications Formentioning
confidence: 99%
“…There are some studies which declare that using FNA in MNG had been unnoticed for more than 80% of carcinomas [28]. In our survey, incidental malignancy within the pathology specimen was determined in 16 patients.…”
Section: Discussionmentioning
confidence: 92%
“…The usefulness of FNA in multi-nodular goiter is controversial. Recently, Antonio Rios et al [15] reported that FNA is not useful for differentiating MNG with malignant degeneration from benign MNG, as more than 80 % of carcinomas go unnoticed. Al-Yaarubi et al [16] mentioned that sensibility and specificity of FNA in determination of malignancy in MNG cases are 16 and 97 %.…”
Section: Discussionmentioning
confidence: 99%